Determination of state of avalanche protection gallery during seismic impact and avalanches - Abdujabarov Abdukhamit; Begmatov Pardaboy; Eshonov Farkhod; Mekhmonov Mashkhurbek; Khamidov Maqsudjon (E3S Web of Conferences, 2023)
The article considers the definitions of the state of the avalanche protection gallery under seismic impact and avalanches. Determined emerging horizontal and vertical vibrations of the entire structure. A calculation scheme was developed to study the dynamics of loose bodies. The scheme of vibrations of a reinforced concrete gallery with an arch covering with backfill soil during a possible earthquake in the OYZ plane is considered. The main type of vibration is lateral, vertical dynamic forces in the ground backfill. The dependence of horizontal forces on the snow layer, the dependence of the force Fr on the gallery on the speed of avalanche movement, the dependence of the force Fr on the unevenness of the backfill soil, and the change in the frequency characteristics of the gallery on the speed of avalanche movement were determined.